The implications of variability in the instruction and practice of the Rinne test - Shauna Maty; Kristen Salana; Robert Hage (Elsevier, 2020)
Purpose: Prior to graduation, all medical students are expected to master the delivery of two basic hearing examinations: the Rinne and Weber tuning fork tests. Throughout basic science years, these tests are routinely examined to determine student competency in clinical skills. However, there exists a high level of variation between practitioners in their modes of implementing these examinations. Materials and methods: Utilizing online databases, YouTube and PubMed, the phrases "Rinne tuning fork test" and "Weber tuning fork test" were searched to find instructional guidelines on how to perform these hearing examinations. Each medium was assessed on five different parameters related to clinical implementation of the hearing exam. In total, 31 of 35 videos met inclusion criteria with views ranging from 1,000 to 1,100,000 and were subsequently assessed for data collection. Results: Through our research investigating instructional video resources of the Rinne test, as well as guidelines in textbooks and journal articles, we were able to determine the major source of incongruity in the instructional process. Of the 31 videos analyzed, bone conduction was tested prior to air conduction in 30 of the 31 videos, while 20 of 31 practitioners held the fork tines parallel to the axis of hearing with the point of reference being the external auditory canal. Only 3 of 31 videos provided guidance regarding the distance the tuning fork should be held away from the patient. A high level of variability exists concerning the purported best approach to testing air and bone conduction in the educational materials available. Conclusion: After reviewing and cross-referencing multiple sources from different mediums, the conclusion was drawn that specific parameters of delivery did not impact the diagnostic reliability of the Rinne test. The major commonality amongst these educational sources was that patients must be able to identify air conduction being louder that bone conduction in order to have a "positive" Rinne test. Given the high level of discrepancy that exists and the likelihood that these examinations will be replaced by audiometry, are these screening tests necessary to teach medical students? Keywords: Rinne test, Weber test, Hearing test, Medical education, Audiometry